Analysis of Elementary School Students Activity in Math Instruction Based on Kurtacil and Beemmath Gamification - Widodo, Suprih; Rahayu, Puji (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This research is motivated by the importance of multiplication operation ability for elementary school students. Thisresearch intend to analyze the activity of elementary school students in math instruction based on kurtacil andbeemath gamification. The research method used is mixed method research and the sample of this research is the 3rdgraders of elementary school students in Purwakarta Regency. The results of this study indicate that there is anexcellent improvement in student learning activity, responses and student perceptions of mathematical instructionbased on kurtacil and Beemmath gamification. The students y feel happy learning math with the game.